Mechanized sowing of mat type paddy nursery for mechanical transplanting - Modi, Rajesh U; Manes, G S; Mahal, J S; Dixit, Anoop Kumar; Singh, Arshdeep (Indian Farming, 2022)
Mat type nursery is a pre-requisite for mechanical paddy transplanting. Raising mat type nursery manually in open field requires many operations in series, starting from soil bed preparation to uprooting of grown up seedlings. It considerably consumes both labour and time with higher human drudgery. However, skill for raising mat type nursery in the field is the major bottleneck in the adoption of mechanical paddy transplanters in India. Hence, farmers are reluctant to raise nursery in this method. Also, the mechanization level is low (20%) in sowing/transplanting as compared to all other farm operations in paddy cultivation. Thus, Punjab Agricultural University, Ludhiana has developed a machine which is capable of accomplishing all the sowing operations required in mat type nursery in one go and can help in timely and uniform sowing of nursery for paddy. The developed machine is a forerunner to mechanical transplantation, which will avoid bending postures and rear walking.